The effectiveness of strategies to contain SARS-CoV-2: Testing, vaccinations, and NPIs - Janos Gablera; Tobias Raabe; Klara Maria Röhrl; Hans-Martin von Gaudecker (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
In order to slow the spread of the CoViD-19 pandemic, governments around the world have enacted a wide set of policies limiting the transmission of the disease. Initially, these focused on non-pharmaceutical interventions; more recently, vaccinations and large-scale rapid testing have started to play a major role. The objective of this study is to explain the quantitative effects of these policies on determining the course of the pandemic, allowing for factors like seasonality or virus strains with different transmission profiles. To do so, the study develops an agent-based simulation model, which is estimated using data for the second and the third wave of the CoViD-19 pandemic in Germany. The paper finds that during a period where vaccination rates rose from 5% to 40%, rapid testing had the largest effect on reducing infection numbers. Frequent large-scale rapid testing should remain part of strategies to contain CoViD-19; it can substitute for many non-pharmaceutical interventions that come at a much larger cost to individuals, society, and the economy.
Keywords: C63; I18; 330; CoViD-19; agent based simulation model; rapid testing; nonpharmaceutical interventions